FACTORS ASSOCIATED TO PATELLAR TENDINOSIS IN ATHLETES: PROVIDING A BASE FOR INJURY MECHANISM AND PREVENTION. Issue 7 (11th March 2014) - Mendonça, L; Fonseca, S; Bittencourt, N; Ocarino, J; Gonçalves, G; Verhagen, E
Abstract : Background: Patellar tendon abnormalities (PTA) are frequent in volleyball and basketball athletes. Tendon degeneration happens through chronic process, related to the amount of stress applied in musculoskeletal system. An appropriated mechanical behaviour of lower limb may be key factor to properly distribute forces in patellar tendon during landing. Identify biomechanical factors associated to patellar tendinosis process could guide preventive attitudes to athletes in risk of chronic dysfunction and/or tendon rupture. Objective: To investigate the association of lower limb biomechanical factors to patellar tendon morphological abnormalities at ultrasound. Design: Cross-sectional. Setting: Institutional clinical care and sports facility. Participants: 35 basketball and volleyball athletes participating on preseason assessment with mean age of 24.0±5.7 years, body mass of 88.9±13.3 kg and height of 1.9±0.1 m. Risk factor assessment: Ankle dorsiflexion range (ADR), shank-forefoot alignment (SFA), iliotibial band flexibility (IBF), hip lateral rotators and abductors isometric strength, hip passive medial rotation range, patellar rotation and knee alignment in the frontal plane were measured during preseason assessment. Ultrasonographic evaluation was performed in both patellar tendons in longitudinal and transverse planes. Main outcome measurements: Patellar tendon hypoechoic areas and thickness at ultrasound. Results: The results showed that low ADR, high IBF and high SFA were associated to PTA. These three variables presented significant areas under ROC curve (P=.008; P=.011; P=.012, respectively). Based on ROC curve sensitivity and specificity values, cut-off points were determined. SFA presented the highest OR; 13.1 (2.1–296); with a cut-off point of 20 o . ADR (cut-off point=36 o ) presented an OR of 4.10 (1.3–13.5) and IBF (cut-off point=-0.04 o ) presented an OR of 4.53 (1.2–21.6). Conclusions: High shank-forefoot varus alignment, ankle dorsiflexion restriction and iliotibial band flexible were associated to PTA. These results show that biomechanical factors could participate on patellar tendon mechanical overload in athletes.